Different Strokes for Different Folks: The BodyMind Approach as a Learning Tool for Patients With Medically Unexplained Symptoms to Self-Manage - Payne, Helen; Brooks, Susan (Frontiers in Psychology, 2018)
Medically unexplained symptoms (MUS) are common and costly in both primary and secondary health care. It is gradually being acknowledged that there needs to be a variety of interventions for patients with medically unexplained symptoms to meet the needs of different groups of patients with such chronic long-term symptoms. The proposed intervention described herewith is called The BodyMind Approach (TBMA) and promotes learning for self-management through establishing a dynamic and continuous process of emotional self-regulation. The problem is the mismatch between the patient’s mind-set and profile and current interventions. This theoretical article, based on practice-based evidence, takes forward the idea that different approaches (other than cognitive behaviour therapy) are required for people with MUS. The mind-set and characteristics of patents with MUS are reflected upon to shape the rationale and design of this novel approach. Improving services for this population in primary care is crucial to prevent the iterative spiralling downwards of frequent GP visits, hospital appointments, and Accident and Emergency attendance, all of which are common for these patients. The approach derives from embodied psychotherapy (authentic movement in dance movement psychotherapy) and adult models of learning for self-management. It has been developed from research and practice-based evidence. In this article the problem of MUS in primary care is introduced and the importance of the reluctance of patients to accept a psychological/mental health referral in the first instance is drawn out. A description of the theoretical underpinnings and philosophy of the proposed alternative to current interventions is then presented related to the design, delivery, facilitation and educational content of the programme. The unique intervention is also described to give the reader a flavour.